2020
DOI: 10.1007/s13762-020-02938-z
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccessibility of metals in soils surrounding two dismissed mining sites in Northern Italy

Abstract: Mining activities are one of the main contributors to metals contamination of soils, most often due to the inappropriate management of the mining residues. In Italy, hundreds of small mining sites are scattered around the mountainous areas, near small villages with fragile environments. Here, wastes and residues may have polluted the surrounding soils and become a threat to living organisms. We investigated two dismissed sites in Northern Italy with extractive wastes in unmanaged areas close to villages using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 36 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…
Fig. 1 Geographic location of the sampling points (background image: Google, Digital Globe, 2018), adapted from Padoan et al ( 2020 )
…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…
Fig. 1 Geographic location of the sampling points (background image: Google, Digital Globe, 2018), adapted from Padoan et al ( 2020 )
…”
Section: Methodsmentioning
confidence: 99%
“…The waste rock dumps have not been remediated after the conclusion of the mining activities. The mining debris were then scattered across the surrounding areas during and after the very long period of exploitation and now most of the slope appears to be heavily contaminated, particularly around the former dumping areas, with Cd concentrations in the topsoil between 13 and 493 mg/kg and Zn values in the range 9–132 g/kg (Padoan et al 2020 ). After the dismissal of the mining operation, the entire area was open to tourism and agriculture and pastures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heavy metals are of great concern because, unlike organic pollutants, they remain unaffected during the degradation of waste, thereby having adverse impacts on living organisms ( Esakku et al., 2003 ; Hogland et al., 2014 ; Jain et al., 2005 ; Mehta et al., 2019 ; Ngole-Jeme and Fantke, 2017 ). Some metals such as, Cd, Cr, and Pb are well known to be toxic to human health, even at very low concentrations ( Adewumi and Laniyan, 2020 ; Csavina et al., 2012 ; Padoan et al., 2020 ), and can pose carcinogenic risks ( Bhatti et al., 2020 ; Gujre et al., 2021 ; Kamunda et al., 2016 ; Thongyuan et al., 2020 ). Exposure to such heavy metal concentrations may lead to numerous health problems, particularly in susceptible individuals, including the elderly and children ( Briki et al., 2017 ; Csavina et al., 2012 ; Dubey et al., 2012 ; Kamunda et al., 2016 ; Stewart, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…A critical review of studies on LFM revealed that research has primarily focussed on material and energy recovery ( Dino et al., 2018 ; Gutiérrez-Gutiérrez et al., 2015 ; Mehta et al., 2020 ; Pecorini and Iannelli, 2020 ). However, there is a fundamental lack of understanding of how these activities could affect the environment and human health ( Frändegård et al., 2013 ; Nguyen et al., 2018 ; Padoan et al., 2020 ). Therefore, this study considered such environmental and human health impacts.…”
Section: Introductionmentioning
confidence: 99%